2018
DOI: 10.1093/biolre/iox182
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 22 prevents lipopolysaccharide- induced preterm labor in mice†

Abstract: Preterm birth is widespread and causes 35% of all neonatal deaths. Infants who survive face potential long-term complications. A major contributing factor of preterm birth is infection. We investigated the role of interleukin 22 (IL22) as a potential clinically relevant cytokine during gestational infection. IL22 is an effector molecule secreted by immune cells. While the expression of IL22 was reported in normal nonpregnant endometrium and early pregnancy decidua, little is known about uterine IL22 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…Although little is known about the IL-22-dependent mechanisms implicated in the female genital tract regarding maintenance of ovarian and uterine function, it is assumed that IL-22 contributes significantly to female reproductive health and has a generally protective nature within this set of organs. Furthermore, IL-22 has been reported to play a role in combating sexually transmitted infections (STIs), intrauterine infections and also contributes to factors involved in pregnancy maintenance [ 112 , 113 , 114 ].…”
Section: Il-22 In the Female Genital Tractmentioning
confidence: 99%
See 2 more Smart Citations
“…Although little is known about the IL-22-dependent mechanisms implicated in the female genital tract regarding maintenance of ovarian and uterine function, it is assumed that IL-22 contributes significantly to female reproductive health and has a generally protective nature within this set of organs. Furthermore, IL-22 has been reported to play a role in combating sexually transmitted infections (STIs), intrauterine infections and also contributes to factors involved in pregnancy maintenance [ 112 , 113 , 114 ].…”
Section: Il-22 In the Female Genital Tractmentioning
confidence: 99%
“…Uterine NK cells (uNK) also make up a large proportion of immune cells in decidual tissues during these two stages [ 118 ]. Interestingly, uNK cells have been found to produce IL-22 in the decidual tissues, and production is significantly upregulated in tissues of pregnant mice after local challenge with lipopolysaccharide (LPS), an unspecific endotoxin that stimulates immune reactions [ 113 , 114 ]. Another report by Gibbs et al has provided evidence that mucosal associated invariant T cells (MAIT) cells are present in cervical tissue, and are also responsible for upregulated IL-17 and IL-22 production in response to Escherichia coli [ 123 ].…”
Section: Il-22 In the Female Genital Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is reported that decidual LTi-like cells may participate in the development of gestational diabetes and chronic diabetes via secreting IL-17 [86]. Recently, the effect of IL-22 in the prevention of lipopolysaccharide-induced preterm labor in mice was revealed and, thus, presents a potential protective role of decidual NCR + ILC3s in inflammation-induced preterm birth [171]. However, decidual ILC2s may play the opposite role in preterm birth due to the increase in ILC2s in the decidua basalis with spontaneous preterm labor compared to non-labor controls [46].…”
Section: Other Pregnancy-associated Diseasesmentioning
confidence: 99%
“…Interleukin-22 knockout (IL-22 À/À ) mice were laboratory-generated as described before (Dambaeva et al, 2018). For generating an IL-22 knockout spontaneous breast cancer mouse model, IL-22 wild-type (IL-22 +/+ ) or IL-22 À/À mice (C57/B6) were crossed with mouse mammary tumor virus-polyomavirus middle T antigen (MMTV-PyMT) transgenic mice (FVB; Jackson Laboratories, Bar Harbor, ME, USA).…”
Section: Generation Of Il-22 à/à /Pymt Micementioning
confidence: 99%